Cases and things around Nora, or where the theater can go when a woman slamm the door behind her - Romano, Lucia [UNESP] (Univ Estado Santa Catarina-udesc, 2018)
In this present text, we analyze national theatrical performance inspired by Henrik Ibsen's The Dolls House, in order to observe how they allowed a more libertarian perspective for women, considering variations on the way they present the fictional status of the protagonist female character, Nora, as well as recourses to destruct some of the pillars of the more traditional dramatic model (whether in terms of the dramaturgical approach, the inventions of the scene and its semiosis, and the relation between the fictional framing and the historical context of the performance). It will be rubbed some performances accomplished from 2009 to 2018, especially in Rio de Janeiro and Sao Paulo, observing as paradigmatic cases the experiences of the Cia Temporaria de Investigacao Cenica, in And Now, Nora?, directed by Joana Doria, and the direction of Regina Galdino for Casa de Bonecas - 2, produced and carried out by Marilia Gabriela, from the text of Lucas Hnath. The pieces represent two contrasting examples of the relationship between feminism, theatrical scene and the creation of women, and are treated here as poles of a (tense) line of possible creative choices, allowing to raise elements that define a different theater through the emphasis on the struggle for equality between men and women.
Keywords: feminist theater; female character; women's production; Henrik Ibsen